Prognostic significance of plasma D-dimer levels in patients with lung cancer - Osamu Taguchi; Esteban C. Gabazza; Hironobu Yasui; Tetsu Kobayashi; M. Yoshida; Hirofumi Kobayashi (1997)
BACKGROUND: The peripheral blood concentrations of several proteases of the clotting system have been shown to predict survival in patients with malignancy. A study was undertaken to investigate the independent value of the plasma levels of the D-dimer degradation product of fibrin before treatment for predicting prognosis in patients with lung cancer. METHODS: The study comprised 70 patients with lung cancer (49 non-small cell lung cancer and 21 small cell lung cancer). Plasma levels of D-dimer were measured using an enzyme immunoassay kit. Multivariate statistical analysis was carried out using the Cox's proportional hazards model. RESULTS: The median value of the plasma level of D-dimer differentiated two groups of patients with different outcomes: a group with a D-dimer level of < 150 ng/ml (low DD group) and those with D-dimer levels of > or = 150 ng/ml (high DD group). Survival time was significantly better in patients in the low DD group than in those in the high DD group in all patients (hazard ratio for high DD group = 4.7; 95% confidence interval (CI) 1.8 to 11.7). The plasma levels of D-dimer predicted survival independently from the clinical stage of disease, histological type, performance status, and tumour size (hazard ratio = 3.9; 95% CI 1.6 to 9.2). CONCLUSIONS: These results suggest that plasma levels of D-dimer might be useful for predicting the clinical outcome in patients with lung cancer. However, further prospective studies are needed in a larger population to confirm these findings.